2021
DOI: 10.1016/j.molcel.2021.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic and phosphoproteomic landscape of KRAS mutant cancers identifies combination therapies

Abstract: Highlights d A proteomic and phosphoproteomic landscape of 43 KRAS mutant cancer cell lines d Multi-omic analysis reveals three subsets with distinct characteristics d Compensatory phosphoprotein biomarker analysis identifies new drug combinations d DOT1L and SHP2 inhibition synergistically treats a subset of KRAS mutant cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Finally, a study of Liu et al (2021 ) showed that DOT1L inhibition, combined with SHP2 blockade, represents an effective means for the treatment of a subset of KRAS-mutant cancers from different tissues. This was demonstrated by the application of the integrative analysis of phosphoproteome and drug sensitivity generated for a group of KRAS-mutant cancer cell lines with distinct biological, clinical, and therapeutic characteristics, representative of tumors with the poorest prognosis.…”
Section: Mechanisms Of Dot1 Action In Solid Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a study of Liu et al (2021 ) showed that DOT1L inhibition, combined with SHP2 blockade, represents an effective means for the treatment of a subset of KRAS-mutant cancers from different tissues. This was demonstrated by the application of the integrative analysis of phosphoproteome and drug sensitivity generated for a group of KRAS-mutant cancer cell lines with distinct biological, clinical, and therapeutic characteristics, representative of tumors with the poorest prognosis.…”
Section: Mechanisms Of Dot1 Action In Solid Tumorsmentioning
confidence: 99%
“…In detail, combination of the two drugs resulted in synergetic inhibition of patient-derived xenograft growth, characterized by an acceptable toxicity level. Further analysis revealed that the observed beneficial effect was associated with DOT1L blockade-induced upregulation of PREX1, which in turn activated MAPK signaling and enhanced vulnerability of tumor cells to SHP2 inhibition ( Liu et al, 2021 ).…”
Section: Mechanisms Of Dot1 Action In Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no published information about the potential role of phosphatases regulating DNMT1. Further, although the potential for methyltransferase DOT1L as a therapy target in KRAS mutant cancers was recently demonstrated (Liu, Liu et al, 2021), currently there is neither information whether RAS regulates DOT1L phosphorylation, nor any indications for the role of phosphatases on DOT1L phosphoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Another study that combined proteomics with genetic interactions mapping identified novel KRAS interactors of which at least two, RAP1GDS1 and RHOA were selectively required for KRAS‐mutant LUAD [ 119 ]. Other approaches have revealed new drug combinations that were specifically vulnerable to KRAS ‐mutant tumors such as inhibition of DOTL1 and SHP2 [ 120 ] or WEE1 and ERK [ 121 ]. Taken together, these studies highlight the fact that proteomic or proteogenomic analyses can reveal novel vulnerabilities which may prove particularly useful in those tumors that do not respond to any of the strategies described above or in cases of resistance to targeted therapies.…”
Section: Identification Of Novel Vulnerabilities Via Proteogenomic St...mentioning
confidence: 99%